2022
DOI: 10.3390/ijms24010072
|View full text |Cite
|
Sign up to set email alerts
|

Old and Promising Markers Related to Autophagy in Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is one of the first causes of death and disability in the world. Because of the lack of macroscopical or histologic evidence of the damage, the forensic diagnosis of TBI could be particularly difficult. Considering that the activation of autophagy in the brain after a TBI is well documented in literature, the aim of this review is to find all autophagy immunohistological protein markers that are modified after TBI to propose a method to diagnose this eventuality in the brain of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…The role of autophagy in TBI has been highly controversial, with many studies demonstrating both its protective and detrimental effects 84–86 . While Beclin1 is a protein important for induction of autophagy, microtubule‐associated protein 1A/1B‐light chain 3 (LC3) plays a key role in the accumulation of autophagosomes 87 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of autophagy in TBI has been highly controversial, with many studies demonstrating both its protective and detrimental effects 84–86 . While Beclin1 is a protein important for induction of autophagy, microtubule‐associated protein 1A/1B‐light chain 3 (LC3) plays a key role in the accumulation of autophagosomes 87 .…”
Section: Resultsmentioning
confidence: 99%
“…The role of autophagy in TBI has been highly controversial, with many studies demonstrating both its protective and detrimental effects. [84][85][86] While Beclin1 is a protein important for induction of autophagy, microtubule-associated protein 1A/1B-light chain 3 (LC3) plays a key role in the accumulation of autophagosomes. 87 Reduction in the hippocampal expression of Beclin1 and LC3 proteins by nutritional supplementation with resveratrol, however, was found to be beneficial in the context of recovery from TBI.…”
Section: Autophagy Marker Expression In the Hippocampus Is Modulated ...mentioning
confidence: 99%
“…Beclin1, similar to yeast Atg6/Vps30, participates in the initiation phase of early autophagosome formation, whereas Atg5 plays an essential role in phagophore elongation. These proteins function as indicators of the initiation and elongation phases of autophagic flux [ 42 , 43 ]. Western blotting revealed that the protein levels of Beclin1 and Atg5 significantly increased during the super-early stage after TBI.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to tell the difference between primary injury, which is caused by external forces striking the skull directly, and secondary injury, which happens as the lesion worsens as a result of cellular damage such ischemia and edema. 1 According to research, the pattern of functional impairments and the course of recovery depend on the severity of the initial damage and, in the case of mild traumatic brain injury (mTBI), the number of impacts received. Multiple cognitive processes, including learning and memory, attention, and processing speed, are impacted by a single mTBI.…”
Section: Introductionmentioning
confidence: 99%